TATBIQU TA’LIM AL ASHWAT AL AROBIYYAH ‘ALA AL MANHAJ AD DIROSY 2013 BI MADROSATI ATSANAWIYYAH - Ali Fathur Rahman; Baiq Raudatussolihah (El-Tsaqafah : Jurnal Jurusan PBA, 2022)
This study examines application of Arabic Ashwat Learning based on the 2013 curriculum at MA Palapa Nusantara East Lombok. The aim of the study was to analyze the strategy for implementing Arabic Ashwat learning in Madrasahs at MA Palapa Nusantara East Lombok and to find out and analyze the influence of Arabic ashwat learning based on the 2013 curriculum at MA Palapa Nusantara East Lombok. This research use desciptive qualitative approach. The data collection method used is the method of observation, interviews, and documentation to obtain data or information related to Arabic Ashwat Learning at MA Palapa Nusantara East Lombok. Teaching sounds, not only in studying sound material for Arabic, in every educational subject there must be teaching sounds, teaching sounds is mandatory for all Arabic language teachers to continue to apply and continue in all their lessons. Arabic aswat learning at Palapa Nusantara school has implementation based on the curriculum, in which the teacher directs and applies orderly learning starting from the opening, reviewing previous learning, learning, question and answer, practice, and assignments.